Comparing linear and bilinear models on water level for the Kelantan river in Malaysia - Azami Zaharim,; Mohd Sahar Yahya,; Ibrahim Mohamed,; Abdul Halim Ismail,; Zuhairuse Md Darus,; Zulkifli Mohd Nopiah, (2005)
Slirveyed from 160 time series data used in scientific articles concluded that 10-13% of them were generated by the nonlinear process. Several nonlinear models are available but only the bilinear model will be considered here. The bilinear model is basically an extension of the linear model ARIMA. It was first introduced by control theorists in 1972 before it was documented by Granger and Anderson in 1978. The bilinear model is believed to be able to fit hydrological and meteorological data well. In this paper; the coefficients of a special case of bilinear model, BL(1,1,1,1), are estimated using nonlinear least squares method. Results of modeling the linear and bilinear models on water level data from the Kelantan river in Malaysia when compared and evaluated gave better fitting to the bilinear model